2019
DOI: 10.1002/adsc.201900660
|View full text |Cite
|
Sign up to set email alerts
|

Site‐selective Oxidative Dearomatization of Phenols and Naphthols into ortho‐Quinols or Epoxy ortho‐Quinols using Oxone as the Source of Dimethyldioxirane

Abstract: A novel reactivity of dimethyldioxirane, generated in situ from Oxone and acetone, with substituted phenols and naphthols is reported. This methodology allowed the synthesis of ortho-quinols or epoxy ortho-quinols from a site-selective oxidative dearomatization process, with good yields under very mild conditions. A short total synthesis of natural product lacinilene C methyl ether is also described using this process as the key step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Because extensive decomposition was observed during the ensuing epoxidation of 22a – 22d when using m -CPBA, other reaction conditions were investigated. After some experimentation using dibenzocycloheptenol as a model, treating the methyl ether 23a with dimethyldioxirane (DMDO) , gave the epoxide, which, without purification, furnished 16 in 65% and 17 in 9% yields over two steps. Ideally, a suitable protecting group (P) of the alcohol, which was required to avoid concurrent oxidation during the DMDO-mediated epoxidation, should also facilitate the C–OP bond cleavage during the semipinacol rearrangement.…”
Section: Resultsmentioning
confidence: 99%
“…Because extensive decomposition was observed during the ensuing epoxidation of 22a – 22d when using m -CPBA, other reaction conditions were investigated. After some experimentation using dibenzocycloheptenol as a model, treating the methyl ether 23a with dimethyldioxirane (DMDO) , gave the epoxide, which, without purification, furnished 16 in 65% and 17 in 9% yields over two steps. Ideally, a suitable protecting group (P) of the alcohol, which was required to avoid concurrent oxidation during the DMDO-mediated epoxidation, should also facilitate the C–OP bond cleavage during the semipinacol rearrangement.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the group of Urbano also reported the synthesis of (±)‐ 81 by simply treating 88 with dimethyldioxirane generated in situ from acetone and Oxone (Scheme 12). [41c] …”
Section: Ortho‐quinols In (Bio)chemical Synthesis Of Natural Productsmentioning
confidence: 99%
“…Till date, a myriad of versatile synthetic strategies has been discovered and labelled in the literature for carrying out such valued transformations. For example, oxidative dearomatization of phenols and naphthols can generate the valuable para ‐ and ortho ‐quinol derivatives which itself has tendency to produce a vast variety of heterocyclic molecules e. g. ortho ‐quinols with different dienophiles in a [4+2]‐manner of many natural products such as wasabidienone B1, grandifloracin, epoxysorbicillinol and so on [458–466] . To this context, More and Ramana studied the production of natural products consisting chroman as well as tetrahydronaphthalene frameworks.…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…For example, oxidative dearomatization of phenols and naphthols can generate the valuable para-and ortho-quinol derivatives which itself has tendency to produce a vast variety of heterocyclic molecules e. g.ortho-quinols with different dienophiles in a [4 + 2]-manner of many natural products such as wasabidienone B1, grandifloracin, epoxysorbicillinol and so on. [458][459][460][461][462][463][464][465][466] To this context, More and Ramana studied the production of natural products consisting chroman as well as tetrahydronaphthalene frameworks. The authors have reported oxone-mediated dearomatization of benzofuran to o-quinone methides (o-QMs) followed by intramolecular [4 + 2]-cycloaddition with a variety of dienophiles like aldehydes, ketones, and olefins to expeditious construction of central [6,6,6,6]-tetracyclic core of integrastatins, epicoccolide A, and epicocconigrone A, (Scheme 196).…”
Section: Oxidative Dearomatization Of the Aromatic Systemsmentioning
confidence: 99%